Upsilon production and polarization in p p macro collisions at square root of s = 1.8 TeV. - Acosta, D; Affolder, T; Akimoto, H; Albrow, MG; Amaral, P; Ambrose, D; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; et al. (2002)
We report on measurements of the Upsilon(1S), Upsilon(2S), and Upsilon(3S) differential cross sections (d(2)sigma/dp(T)dy)(/y/<0.4), as well as on the Upsilon(1S) polarization in p p macro collisions at square root of s = 1.8 TeV using a sample of 77+/-3 pb(-1) collected by the collider detector at Fermilab. The three resonances were reconstructed through the decay Upsilon-->mu(+)mu(-). The measured angular distribution of the muons in the Upsilon(1S) rest frame is consistent with unpolarized meson production.